Kipin School Digital Learning Application at Tarbiyatul Islamiyah Jagakarsa Elementary Madrasah School - Ramadhan, Muhammad Azizi; Ohorella, Noviawan Rasyid; Anggraini, Dyah; Yudha, Reza Praditya (COMMUSTY Journal of Communication Studies and Society, 2025)
This study aims to analyze how the use and utilization of the Kipin School application supports the learning process at Madrasah Ibtidaiyah Tarbiyatul Islamiyah. This application provides various educational features that can help students and teachers improve the quality of learning, as well as support access to more interactive and easily accessible teaching materials. In this study, the theory used is the theory of technological determination, which emphasizes that technological developments have a dominant influence in shaping social change, including in the world of education. This study uses a qualitative method with a descriptive approach. The paradigm used in this study is the constructivist paradigm. Data collection techniques include in-depth interviews, observations, documentation, and literature studies. The results of the study indicate that the use and utilization of the Kipin School application plays an important role in supporting the learning process at Madrasah Ibtidaiyah Tarbiyatul Islamiyah. This application helps improve access to teaching materials, enriches learning methods, and encourages more active interaction between teachers and students in teaching and learning activities.